Efficacy of immune checkpoint inhibitors in EGFR-Mutant NSCLC patients with EGFR-TKI resistance: A systematic review and meta-analysis - Qian, Xiaoyu; Guo, Xiaodan; Li, Ting; Hu, Wei; Zhang, Lin; Wu, Caisheng; Ye, Feng (Frontiers in Pharmacology, 2022)
Background Epidermal growth factor receptor (EGFR) mutations are common in patients with non-small-cell lung cancer (NSCLC), particularly in Asian populations. Tyrosine kinase inhibitors (TKIs) are a first-line treatment in patients with mutant EGFR, but their use is often accompanied by drug resistance, which leads to disease progression. Chemotherapy and immunotherapy are the main treatment options after progression. The efficacy of immune checkpoint inhibitors (ICIs) and their combination therapy in patients with EGFR-TKI resistant is not clear. It is thus necessary to evaluate the efficacy of ICIs and ICI-based combination therapies in patients with EGFR-TKI-resistant NSCLC. Methods We searched for randomized controlled trials (RCTs) comparing ICI therapy alone or in combination versus other therapies using PubMed, the Cochrane Library, Web of Science, EMBASE, MEDLINE, ClinicalTrials.gov, and several international conference databases, from database inception to March 10, 2022. The hazard ratio (HR) and 95% confidence interval (95% CI) for median overall survival (OS) and median progression-free survival (PFS) were evaluated. Odds ratio (OR), risk ratio (RR), and 95% CI were used as effect indicators for objective response rate (ORR) and safety data. Results Seven eligible RCTs were included in the present meta-analysis. The results showed that neither ICIs nor combination therapy prolonged median OS in EGFR-TKI resistant NSCLC patients (HR=1.04, 95% CI: 0.84–1.29, P=0.73). However, compared with the control group, the patients treated with ICI-based combination therapy had better PFS (HR=0.62, 95% CI: 0.45–0.86, P=0.004) and ORR (OR=1.84, 95% CI: 1.28–2.66, P=0.001). Conclusions ICI monotherapy did not improve the OS or PFS of NSCLC patients previously treated with EGFR-TKIs, whereas patients treated with ICI-based combination therapy had better PFS compared with those receiving conventional chemotherapy, indicating that this therapy could be offered to patients with EGFR-mutant NSCLC after progression following TKI treatment. There was no significant difference in all-grade treatment-related adverse events (TRAEs) between the combination therapy group and the control group. However, a higher incidence of discontinuation due to TRAEs was observed; this requires attention in future studies. The results of this meta-analysis provide a reference for clinical practice and future trial design. PROSPERO registration number: CRD42021282207